KESIAPAN TATA KELOLA PUSKESMAS MENJADI BADAN LAYANAN UMUM DAERAH (BLUD) - Yati Maryati (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
This study aims to determine the readiness of Public Health Centers in Semarang regency to become Public Service Board.This research is qualitative research which is presented through descriptive exploratory. Key informants of this study were the Head of Public Health Center and the Head of Administration from four Public Health Centers in Semarang regency. The data were collected through in-depth interviews and observational research. The data were analyzed by using content analysis.The results showed that the requirements of administrative preparation for Public Health Center becoming Public Service Board has been arranged as follows: statement letter of readiness, governance patterns, and minimum service standards. Outpatient and Inpatient of Public Health Centers in Semarang regency have differences in the funding aspect. All of Public Health Centers wish to have best quality services, by the existence of Public Service Board people hope for better finances management so it can improve the quality of health service at the Public Health Centers. Therefore, the commitments of internal staff of Public Health Centers need to be raised/enhanced to create an atmosphere that supports the readiness of implementing the policy of Public Health Center as Public Service Board in Semarang regency.